The development and assessment of a fixed dose combination tablet of Ranitidine and Metronidazole - King'ori, Loti David (Rhodes University, Faculty of Pharmacy, Pharmacy, 2011)
The oral route of drug administration is convenient since it is acceptable to most patients and the manufacturing processes used to produce tablets and capsules are relatively simple when compared to those used to manufacture other types of dosage forms. Metronidazole (MTZ) and Ranitidine (RTD) have been used in combination, as part of triple therapy for the treatment of ulcers. However the use of large numbers of tablets and long duration of therapy makes adherence to drug treatment challenging for patients. Therefore the formulation of a fixed dose combination (FDC) of MTZ and RTD may improve patient adherence to therapy and consequently may reduce morbidity and mortality due to ulcers. A stability indicating HPLC method for the simultaneous analysis of MTZ and RTD was developed and validated according to the International Conference on Harmonization (ICH) guidelines. The method was sensitive, selective, precise, accurate and linear.Preformulation studies were performed on the active pharmaceutical ingredients (API) alone and in combination with potential excipients. Differential scanning calorimetry (DSC) studies revealed a potential interaction between MTZ and RTD, however the interaction was not apparent following IR analysis of the same samples. DSC analyses of the API in combination with potential excipients revealed that the compounds were compatible with most materials with the exception of a binary mixture of RTD and Dibasic calcium phosphate (DCP) that exhibited a potential interaction. Thermal gravimetric analysis (TGA) of MTZ and RTD revealed that both compounds exhibited thermal stability. The Carrs Index (CI) and Hausner Ratio (HR) values of MTZ and RTD indicated that both compounds exhibited poor flow and compressibility properties, whereas the CI and HR values for (Microcrystalline cellulose) MCC and DCP indicated better flowability and compressibility characteristics.Direct compression and wet granulation processes were assessed to identify a suitable method of manufacture of FDC tablets of MTZ and RTD. The blends were evaluated using bulk and tapped density and the resultant tablets were evaluated for weight uniformity, crushing strength, tensile strength and disintegration time. The wet granulation method of manufacture produced tablets that showed acceptable pharmacotechnical properties: this approach was therefore used as the method of manufacture of FDC tablets of MTZ and RTD. Tablet formulations comprised of API, viz. MTZ and RTD and different compositions of MCC, DCP, Sodium starch glycolate (SSG) and Croscarmellose sodium (CCS), were manufactured in order to screen for an appropriate diluent and disintegrant composition for use in response surface studies. Assays of tablet content and in vitro drug release were undertaken using the validated HPLC method. Tablets in which MCC and CCS were used appeared to produce better assay and dissolution results as compared to those manufactured using DCP and SSG. Consequently a formulation comprised of MCC and CCS was selected and used in studies in which the effect(s) of level two formulation and composition changes as described in the Scale and Post Approval Changes for Immediate Release (SUPAC-IR) Guidelines on tablet disintegration and in vitro release were assessed. A Box-Behnken statistical design was used for the investigation of the effect of input factors, viz. CCS, (Polyvinyl pyrollidone K30) PVP-K30 and magnesium stearate on measured responses, viz. disintegration time and percent drug release in 10 minutes (Q10). CCS appeared to have an inverse linear relationship on disintegration time and a linear relationship with the Q10 for MTZ and RTD, whereas PVP-K30 and magnesium stearate appeared to have an antagonistic effect on the measured responses. Furthermore CCS and magnesium stearate exhibited an interaction that had an agonistic effect on the Q10 value for RTD. A numerical optimization approach was used to predict a formulation composition that would produce tablets that exhibited a disintegration time and Q10 values for MTZ and RTD that fell within the constraints set in our laboratory. The resultant model was found to be accurate and had a percent prediction error of < 5% for all measured response variables.FDC tablets of MTZ and RTD have been successfully produced. The disintegration of the tablet and dissolution of the API were within compendial specifications and the tablets are of suitable quality and have the potential to be further investigated to reduce the pill burden in the treatment of ulcers.
Keywords: Ulcers -- Treatment; Ranitidine -- Evaluation; Metronidazole -- Evaluation